Pharmacovigilance and pharmaceutical intervention in preventing adverse drug reactions at a hospital in Cascavel-Paraná (Research, Society and Development, 2024)
This study explores the importance of pharmacovigilance for managing Adverse Drug Reactions (ADRs), a significant public health issue. In the United States, ADRs are one of the leading causes of mortality, and in Brazil, the lack of data highlights the need for a proactive approach. The objective was to identify ADRs in a large hospital in Cascavel-PR, using the Trigger Tool Method to demonstrate the importance of pharmacovigilance in improving healthcare quality and preventing errors in subsequent admissions, emphasizing the need to monitor these reactions to avoid new adverse events. Using a cross-sectional, retrospective, and observational approach, 243 patient records were analyzed throughout 2023. A total of 26 ADRs were identified, predominantly in female patients under 60 years of age. The associated medications were Hydrocortisone (18 cases), Naloxone (4), Allegra (2), and Fenergan (2). The reactions were primarily classified as probable, followed by possible, doubtful, and defined. The most common symptom was itching, and the specialty with the highest number of ADRs was General Medicine. The analysis confirmed the effectiveness of the Trigger Tool Method in identifying ADRs, highlighting the need for pharmacovigilance methods to gain a more detailed view of adverse reactions. The results emphasize the importance of proactive clinical pharmacist intervention in detecting and documenting ADRs to ensure patient safety and prevent future events. Expanding research to other institutions and conducting multicenter studies is recommended to enhance pharmacovigilance practices.